Developing an accessible learning application for sign language (B) - Rachman, Steven (Nanyang Technological University, 2022)
Deaf people have a hard time communicating with their family members, and this is mostly due to the lack of experience of their family members in using sign language. Accessible learning resources for sign language in the market are still limited, and this project proposes a new solution for an easy and accessible way to learn sign language by utilizing 3D avatars and a real-time sign recognition feedback system. This report discusses the implementation of the 3D avatar using three.js and React, including with the implementation of the real-time sign recognition system by utilizing MediaPipe and WebSocket.